Neuroblastoma in a newborn infant - H. Tjandra; E. Sarwono; E. H. Tambayong (Indonesian Pediatric Society, 1981)
The incidence of neuroblastoma, one of the most common malignant neoplasms in infants and children is greatest at the age of two years; but occasionally is diagnosed at birth. The diagnosis may be simple or very complicated. It is even more difficult when it occurs in the newborn infant. At this age the primary tumor is usually small and undetected. The presenting sign is generally due to the massive hepatomegaly caused by metastasis.In this report we present a rare case of congenital neurablastoma with the sole clinical manifestation of liver enlargement. The difficulties in arriving at a correct diagnosis are emphasized.